Students' Experiences of Meaningful, Mindful, and Joyful Learning in an AI-Enhanced English Classroom - Tariza Dwi Silvania; Abdul Halim; Khusnul Khatimah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This qualitative case study explores tenth-grade students’ experiences of meaningful, mindful, and joyful learning in an AI-enhanced English classroom. Conducted at SMAN 1 Kota Bangun, the research employed classroom observations, open-ended questionnaires, and semi-structured interviews to gather insights into how AI tools such as ChatGPT, Gemini, image generators, and Grammarly shaped students’ engagement, motivation, and learning depth. Thematic analysis revealed that AI supported personalized learning, encouraged self-regulated preparation, and increased motivation through interactive features. However, challenges such as accuracy issues, distractions, and overreliance on AI were noted. Findings suggest that while AI can complement instructional practices and promote deep learning, its optimal use depends on teacher guidance, student digital literacy, and thoughtful integration into classroom pedagogy.